Pengembangan Unit Bisnis Dengan Media Digital Yang Terintegrasi Di UMKM Seroja Pabuaran Barat Pondok Karya - Tangerang Selatan - Petrus Sianggian; Agus Suharto; Rahmat Hartono (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
Community service in Pondok Karya Village, Pondok Aren District, South Tangerang City, was implemented as an effort to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) to face the challenges of the digital era. MSMEs in this area show significant potential in the culinary, craft, and service sectors, but remain limited in the use of digital technology for marketing and business management. This community service activity aims to provide training in digital media and online stores, enabling MSMEs to optimize promotional strategies, expand market access, and increase competitiveness. Implementation methods include outreach, technical training on social media and marketplace use, assistance in online store creation, and business sustainability evaluation. The expected outcomes are increased digital literacy among the community, the establishment of active online stores managed by local MSMEs, and the availability of app-based MSME mapping data as a reference for the village government in policymaking. Thus, this program not only supports local economic strengthening but also serves as a model for technology-based community empowerment that can be replicated in other regions.